PROPORSI PENGELUARAN RUMAH TANGGA PETANI PADI DI DESA PATIMBAN, KECAMATAN PUSAKANAGARA, KABUPATEN SUBANG, JAWA BARAT - Nur Fatimah; Nur Syamsiyah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
Subang Regency is the third rice production center in West Java. Be as a rice production center did not make the resident of Subang Regency to food security. According to production and industry data West Java Province in (2017), Subang Regency received rastra that reached 112.891 KPM. Rastra is one of the instruments to reduce the problem of poverty and food insecurity. This research purposes are to analyze the household characteristic and proportion of household expenditure of rice farmers. This research was conducted in Patimban Village, Pusakanagara Subdistrict, Subang Regency, West Java. The data collecting technique was conducted by the questionnaire with 51 household of rice farmers responden who received rastra using by Simple Random Sampling.  The method of this research used by survey with statistic descriptive analyze to know characteristic and proportion of household expenditure of rice farmer by BPS (2017) consisting of 14 indicators of food and 6 indicators of non-food.  The result show characteristic of the household rice farmers: the average productive age (92%), the education level is elementary school (53%), the status of land as tillers (51%), the average of the land area is 0.75ha, total of dependant family 3-4 peoples (70%), income per month is IDR 3.578.275,00. The proportion of average expenditure per month of household of rice farmer is Rp 2.794.891,00 that consist of Rp 1.667.324,00 for food expenditure and Rp 1.127.567,00 for non-food expenditure.Keywords: Rice, food security, household of farmer, proportion, expenditure